Agricultural mechanics - Herren, Ray V. (Delmar Cengage Learning, 2006)
Agricultural Mechanics: Fundamentals & Applications continues to be the most widely used textbook for high school Agricultural Mechanics programs nationwide because of its student friendly layout and its comprehensive coverage. Topics covered range from welding to tool identification, from diesel engine maintenance to masonry. The units are presented in a logical, easy to follow format allowing students to comprehend concepts and apply them in hands on applications. Objectives and competencies to be developed are included in each section, along with a list of new terms, a materials list, student activities, and self-evaluations. The new fifth edition has been updated throughout to address the changing technologies that help shape the world of agriculture